Materials with the CrVO4 structure type as candidate superprotonic conductors. Issue 55 (8th October 2019) - Wisesa, Pandu; Li, Chenyang; Wang, Chuhong; Mueller, Tim
Abstract : A computational screen reveals that materials with the CrVO4 structure type may have very low migration barriers for proton conduction. Abstract : Proton conducting oxides have the potential to improve the efficiency of solid oxide fuel cells and electrolyzers, yet many oxide structures remain relatively unexplored for the ability to conduct protons. To accelerate the search for novel proton-conducting oxides, we have performed a computational screen of the proton migration energy in 41 different commonly-occurring oxide structure types. The results of this screen, which are supported by a comprehensive set of density functional theory calculations, indicate that known materials with the CrVO4 structure type have an average migration energy for proton diffusion of less than 0.2 eV, with several known materials having calculated migration energies below 0.1 eV. These results indicate that materials with the CrVO4 structure type, which to our knowledge have not been previously explored as candidate proton conductors, may exhibit very high proton conductivity that surpasses that of leading proton-conducting oxides. We present the results of our screen as well as diffusion dimensionality analysis and thermodynamic stability analysis for materials with the CrVO4 structure.